Hooked : how crafting saved my life - Foster, Sutton (Grand Central Publishing, 2021)
In these intimate stories and reflections about how crafting has kept her sane while navigating the highs and lows of family, love, and show business, Tony Award-winner and the star of TV's Younger Sutton Foster shares memorable moments - including her fraught relationship with her agoraphobic mother; a painful divorce splashed on the pages of the tabloids; her struggles with fertility; the thrills she found on the stage; her breakout TV role in Younger; and the joy of adopting her daughter, Emily. Accompanying the stories, Sutton has included crochet patterns, recipes, and so much more.